Preparation of polymer-based cement grinding aid and their performance on grindability. (30th January 2015) - Zhang, Tailong; Gao, Jianming; Hu, Jingchao
Highlights: The process of preparing polymer-based grinding aid was introduced. The structure of polymer-based grinding aid was characterized by FT-IR. The performance of polymer-based grinding aid was determined. The change of shape of ground cement particles was determined by SEM. Polymer-based grinding aids increased the fluidity of ground cement. Abstract: This paper described a chemical process called water-based free radical polymerization to synthesize a polymer-based grinding aid (PGA), which was characterized by infra-red spectroscopy (FT-IR) and used for the production of Portland cement (ground in a ball mill at a laboratory stage). For this purpose, reference cement was also produced without using PGA. All the cement mixtures were tested for specific surface area and particle size distribution. The changes of shape of particles and repose angles of ground cement were also tested to evaluate the flow characteristics of ground cement. Compared to a reference cement admixture, the addition of PGA led to significant gains in specific surface area, a fact that was attributed to the PGA's ability to prevent agglomeration and powder coatings of ball. The results also indicated that PGA had obviously influences on particle size distribution of ground cement, which showed a narrower grading spectrum as the PGA dosage increased. Test results by SEM and repose angle method showed that PGA resulted in improvement of roundness and fineness of cement grains and fluidity of ground cement.